ANALISIS EFEKTIVITAS PENGGUNAAN BAHASA INDONESIA PADA WEBSITE ELEARNING UPN “VETERAN” JAWA TIMUR - Moch. Abdillah Emha Ramdhani; Kevin Yohanes Wuryanto; Andhika Rizky Aulia; Adimas Syiraa Setiabudi; Mirza Khazim Nugraha; Bagus Dwi Putra Adiyono; Dewangga Nanda Arjuna; Endang Sholihatin (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
This study aims 1) to find out whether the use of Indonesian on the elearning website at the Universitas Pembangunan “Veteran” Jawa Timur can support student learning, and 2) to analyze the effectiveness of using Indonesian on elearning at the Universitas Pembangunan “Veteran” Jawa Timur. The method used in this study is a quantitative method using a questionnaire as a data collection instrument. Based on this research, it can be concluded as follows: 1) the use of Indonesian on the elearning website of the Universitas Pembangunan “Veteran” Jawa Timur can support student learning because around 80.73% of respondents stated that they agreed or supported it. Next, 2) the use of Indonesian in elearning at the Universitas Pembangunan “Veteran” Jawa Timur is known to be effective, with answers agreeing and strongly agreeing around 79.45%. Suggestions for further research are to increase the sample of respondents and use other research methods with the aim of producing different outputs. Keywords: effectiveness, elearning, language